Integration of Early Specialist Palliative Care in Cancer Care: Survey of Oncologists, Oncology Nurses, and Patients - Salins, Naveen (Indian J Palliat Care, 2016)
INTRODUCTION: Palliative care is usually delivered late in the course of illness trajectory. This precludes patients on active disease modifying treatment from receiving the benefit of palliative care intervention. A survey was conducted to know the opinion of oncologists, oncology nurses, and patients about the role of early specialist palliative care in cancer. METHODS: A nonrandomized descriptive cross-sectional study was conducted at a tertiary cancer care center in India. Thirty oncologists, sixty oncology nurses, and sixty patients were surveyed. RESULTS: Improvement in symptom control was appreciated by oncologists, oncology nurses, and patients with respect to pain (Z = −4.10, P = 0.001), (Z = −5.84, P = 0.001), (Z = −6.20, P = 0.001); nausea and vomiting (Z = −3.75, P = 0.001), (Z = −5.3, P = 0.001), (Z = −5.1, P = 0.001); constipation (Z = −3.29, P = 0.001), (Z = −4.96, P = 0.001), (Z = −4.49, P = 0.001); breathlessness (Z = −3.57, P = 0.001), (Z = −5.03, P = 0.001), (Z = −4.99, P = 0.001); and restlessness (Z = −3.68, P = 0.001), (Z = −5.23, P = 0.001), (Z = −3.22, P = 0.001). Improvement in end-of-life care management was appreciated by oncologists and oncology nurses with respect to communication of prognosis (Z = −4.04, P = 0.001), (Z = −5.20, P = 0.001); discussion on limitation of life-sustaining treatment (Z = −3.68, P = 0.001), (Z = −4.53, P = 0.001); end-of-life symptom management (Z = −4.17, P = 0.001), (Z = −4.59, P = 0.001); perimortem care (Z = −3.86, P = 0.001), (Z = −4.80, P = 0.001); and bereavement support (Z = −3-80, P = 0.001), (Z = −4.95, P = 0.001). Improvement in health-related communication was appreciated by oncologists, oncology nurses, and patients with respect to communicating health related information in a sensitive manner (Z = −3.74, P = 0.001), (Z = −5.47, P = 0.001), (Z = −6.12, P = 0.001); conducting family meeting (Z = −3.12, P = 0.002), (Z = −4.60, P = 0.001), (Z = −5.90, P = 0.001); discussing goals of care (Z = −3.43, P = 0.001), (Z = −5.49, P = 0.001), (Z = −5.61, P = 0.001); maintaining hope (Z = −3.22, P = 0.001), (Z = −4.85, P = 0.001), (Z = −5.61, P = 0.001); and resolution of conflict (Z = −3.56, P = 0.001), (Z = −5.29, P = 0.001), (Z = −5.28, P = 0.001). Patients appreciated improvement in continuity of care with respect to discharge planning (Z = −6.12, P = 0.001), optimal supply of essential symptom control medications on discharge (Z = −6.32, P = 0.001), follow-up plan (Z = −6.40, P = 0.001), after hours telephonic support (Z = −6.31, P = 0.001), and preferred place of care (Z = −6.28, P = 0.001). CONCLUSION: Oncologists, oncology nurses, and patients felt that integration of early specialist palliative care in cancer improves symptom control, end-of-life care, health-related communication, and continuity of care. The perceptions of benefit of the palliative care intervention in the components surveyed, differed among the three groups.